FUNDRAISING AS A SOURCE OF FUNDING FOR PUBLIC UNIVERSITY LIBRARIES IN KENYA - Ngetich, Festus Kipkorir; Rotich, Daniel C.; Otike, Japheth (Mousaion: South African Journal of Information Studies, 2016)
The aim of this paper is to examine fundraising as a viable supplementary source of funding for public university libraries in Kenya. Ideally, university libraries require sufficient funding in order to effectively play their role which is to support teaching, learning and research activities in the university. However inadequate allocation of funding to public university libraries in Kenya over the years has negatively affected the quality of their services. Therefore there is an urgent need for these libraries to consider fundraising as a source of funding. Using a sample comprising of 84 Librarians and 18 informants from seven public universities in Kenya, this paper established that fundraising, if well planned and coordinated, is a viable supplementary source of funding for public university libraries in Kenya.Â 